A new species of Neosilba (Diptera, Lonchaeidae) associated with fig orchards in Mexico - Macgowan, Iain; Navarro-De-La-Fuente, Laura; Williams, Trevor; Lasa, Rodrigo (Zootaxa, 2025)
A distinctive species of Neosilba Waddill & Weems, namely Neosilba flavitarsis sp. nov is described from specimens reared from cultivated figs in Mexico. DNA sequencing confirms that the species belongs in the genus Neosilba and it is placed in a phylogenetic tree with other close relatives.